The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1109/32.988711
|View full text |Cite
|
Sign up to set email alerts
|

A controlled experiment in maintenance: comparing design patterns to simpler solutions

Abstract: ÐSoftware design patterns package proven solutions to recurring design problems in a form that simplifies reuse. We are seeking empirical evidence whether using design patterns is beneficial. In particular, one may prefer using a design pattern even if the actual design problem is simpler than that solved by the pattern, i.e., if not all of the functionality offered by the pattern is actually required. Our experiment investigates software maintenance scenarios that employ various design patterns and compares d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 5 publications
(4 reference statements)
5
115
1
Order By: Relevance
“…He found that some patterns, such as Observer and Singleton, are correlated with large code structures and are likely to be more fault prone. Prechelt et al [27] performed a series of controlled experiments with the aim of comparing design patterns with alternative, simpler solutions to perform maintenance tasks. They found that the code developed using design patterns contained a lower number of defects than the code developed using alternative design strategies.…”
Section: Design Pattern Fault Pronenessmentioning
confidence: 99%
“…He found that some patterns, such as Observer and Singleton, are correlated with large code structures and are likely to be more fault prone. Prechelt et al [27] performed a series of controlled experiments with the aim of comparing design patterns with alternative, simpler solutions to perform maintenance tasks. They found that the code developed using design patterns contained a lower number of defects than the code developed using alternative design strategies.…”
Section: Design Pattern Fault Pronenessmentioning
confidence: 99%
“…Prechelt et al [18] performed a series of controlled experiments to compare design motifs with alternative, simpler solutions to assess their impact on maintenance tasks.…”
Section: Related Workmentioning
confidence: 99%
“…As a future work, we aim to extract the evolution of such aspect oriented re-factoring changes to show if the code quality improves in time by looking, for example, at defect density. Regarding the analysis of design pattern evolution, Bieman et al [2] analyzed four small size systems and one large size system to identify the observable effects of the use of design patterns, such as pattern change proneness; Vokáč [27] analyzed the corrective maintenance of a large commercial product over three years, comparing defect rates for classes that participated in design patterns versus those that did not participate; Prechelt et al [24] performed a series of controlled experiments with the aim of comparing design patterns with alternative, simpler solutions to perform maintenance tasks.…”
Section: Related Workmentioning
confidence: 99%